Introduction of a formative assessment tool in a post-graduate training program in India: a mixed methods evaluation - Katherine Douglass; Tania Ahluwalia; Brianna McKiernan; Heena Patel; Natasha Powell; Jacob Keller; Serkan Toy (International Journal of Emergency Medicine, 2024)
Abstract Background Our institution has longstanding post-graduate education and training partnership programs in Emergency Medicine (EM) across India. A programmatic challenge has been the integration and uptake of evidence-based medicine and lifelong learning concepts. Formative assessment (FA) is intended to enable learners to monitor learning, identify strengths and weaknesses, and target areas of growth. As part of a program improvement initiative, we introduced an online FA tool to existing summative assessments. This study investigates how the FA tool was used and perceived by trainees. Methods 246 trainees across 19 sites were given access to the FA tool. Usage metrics were monitored over 12 months. Semi-structured interviews were conducted in person with trainees using a purposive sampling methodology. A hybrid thematic analysis approach was used to determine themes. Interviews were coded independently by two blinded researchers using NVivo software. The study was deemed exempt by our institutional review board. Results There was high variability in trainees’ utilization of the FA tool. Trainees who used the FA tool more performed better on summative exams (r = 0.35, p < 0.001). Qualitative analysis revealed that trainees were motivated to learn for improved clinical knowledge and to be a good physician, not only passing exams. Benefits of the tool included the relationship to clinical practice and thorough explanation of answers, while disadvantages included topics unrelated to India. Conclusion The integration of a FA tool has provided positive outcomes for trainees in EM education programs in India. Lessons learned may apply globally to other contexts and programs.